Bibliometric Analysis of Press Freedom: Trends, Patterns, and Key Research Areas - Gita Pratiwi; Hanny Hafiar; Pandan Yudhapramesti (Jurnal Komunikasi dan Bisnis, 2026)
Press freedom serves as a fundamental pillar within a democratic system, ensuring that journalists can perform their role as social watchdogs without the shadow of intimidation. Globally, however, the integrity of this profession faces systemic challenges ranging from physical aggression to repression by state actors and interest groups. This study employs bibliometric analysis to map the evolving landscape of press freedom, identifying key trends, influential actors, and emerging themes within global scholarly literature. A total of 602 peer-reviewed articles indexed in Scopus from 1989 to 2025 were analyzed using Biblioshiny and VOSviewer, revealing a robust annual growth rate of 13.02% with a peak of 82 publications in 2025. The co-word network analysis identifies "Press Freedom" as the most central theme (betweenness centrality = 770.46), bridging critical clusters such as Censorship and Democracy alongside emerging themes of Digital Authoritarianism, Online Harassment, and Disinformation. The study reveals a notable shift towards digital authoritarianism, highlighting how online harassment and disinformation are increasingly used to silence journalists, thereby obstructing their watchdog function and weakening democratic discourse. The findings underline the growing need for comprehensive protection policies that address both physical and digital threats to journalists, ensuring the continued functioning of a free press in a rapidly changing political environment.